(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study explores principals’ leadership attributes. The issue of leadership remains in focus for the placement of principals in line with the Malaysia Education Blueprint (2013-2025). Leadership problems in schools are often associated with student outcomes. Therefore, this explorative qualitative study was conducted in a secondary school with the most outstanding performance. This selection of this school as the setting for this case study was driven by its principal’s leadership. Data were gathered via extended interviews, observations, and item analyses. The thematic analysis of data and findings reveal three attributes of the principal’s leadership namely positive attributes, professionalism attributes, and solidarity attributes as the contributing factors towards the school’s success. The implications of this study show that principals possessing strong attributes are capable of being effective leaders. It is hoped that this study will contribute additional knowledge on leadership among educational administrators.